Minimizing skull defects in retrosigmoid approach: precision mapping of the sigmoid sinus with mastoid emissary vein canal - Artem V. Rozumenko; Mykola V. Yehorov; Vasyl V. Shust; Dmytro M. Tsiurupa; Anton M. Dubrovka; Petro M. Onishchenko; Volodymyr O. Fedirko (Ukrainian Neurosurgical Journal)
Objective. The retrosigmoid approach is a commonly used cranial approach to the cerebellopontine angle lesions, vascular and nerve pathologies. This study aims to develop a practical technique for intraoperative mapping of the sigmoid sinus using the topography of the mastoid emissary vein (MEV) canal to improve the accuracy of retrosigmoid craniotomy, and minimize postoperative adverse outcomes. Materials and methods. Consecutive patients who underwent retrosigmoid approaches for cerebellopontine angle occupying lesions from October 2023 through August 2024 were included in the study. Perioperative computed tomography (CT) was performed with a slice thickness 0.5 mm in the axial plane. The projection of the internal opening of the MEV canal onto the external surface of the mastoid process was determined as the posterior border sigmoid sinus and anterior border for craniotomy. Comparative analyses were performed using t-test and Chi-square test. Results. A total of 20 patients were operated for neoplasms occupying the cerebellopontine angle using retrosigmoid approach. The average measured distance from the external opening of the MEV canal to the projection of sigmoid sinus posterior border was 9.36 ± 2.17 mm (range 6.3–13.20 mm). The postoperative CT data showed statistically significant differences between the study and control groups in measures of bone window (p = 0.057) and surrounding cranial defect (p < 0.001). The size of bone flaps was slightly similar in all groups (p = 0.114). The mean cranial defect in the study group was almost twice smaller than in the control group 22.4% vs. 44.5% respectively. Conclusions. This study confirms the utility of mastoid emissary vein canal topography in improving the accuracy of retrosigmoid craniotomy. By facilitating precise sigmoid sinus mapping, the technique reduces the extent of bone removal and minimizes postoperative cranial defect.